An analysis of Google entry and positioning in Unified Communications for the business customers market - Pierr Vialle (International Telecommunications Society (ITS), 2012)
In this paper, we focus on the telecommunications/computing convergence in business market. While the telecommunications/audio-visual convergence has been extensively analysed from an academic perspective, the telecommunications/computing convergence has drawn less attention. This is also the case in general of the business market as opposed to the consumer market. The business communications market has been deeply transformed by technological and product convergence, due to the progressive substitution of traditional TDM-based voice products and services by ToIP (Telephony over IP) based products and services. The adoption of IP and the management of voice applications in the same way as data application has given rise to convergence offerings under the name of Unified Communications, and allowed the entry of data communications vendors, such as Cisco, in a market initially dominated by TDM-based product vendors. The increasing dissociation between hardware and software and the virtualisation of services have induced the entry of new players relying on their initial position in software and web services, among which Microsoft and Google. Firstly, we present the Unified Communications market and products. Secondly, we analyse how Google's has entered this market and built its product portfolio through acquisitions, in order to identify the dimensions of line extensions and the importance of extensions. Thirdly, it leads us to discuss this strategy as an extension of its two-sided market strategy. This strategy is different from its traditional two-sided market strategy, as it aims at generating other revenues than only advertising. It is also not really a two-sided market, but rather a product versioning relying on direct network externalities. This study is based on documentary research, in particular the systematic analysis of Google's press releases, and on information collected from interviews with market incumbents.
Keywords: 330; Convergence; resources; two-sided market; unified communications; business; communications; Google